What we would like Lhc to give us : proceedings of the International School of Subnuclear Physics - Zichichi, Antonino (Subnuclear series, 2014)
This book is the proceedings of the International School of Subnuclear Physics, ISSP 2012, 50th Course - ERICE, 23 June 2013 - 2 July 2012. This course was devoted to the celebrations of the 50th Anniversary of the Subnuclear Physics School which was started in 1961 by Antonino Zichichi with John Bell at CERN and formally established in 1962 by Bell, Blackett, Weisskopf, Rabi and Zichichi in Geneva (CERN). The lectures covered the latest and most significant achievements in theoretical and in experimental subnuclear physics.